VIOLA-AS-FISH: AN ECOFEMINIST ANALYSIS OF TWELFTH NIGHT - Cardoso, Raissa Furlanetto (REVISTA DE LETRAS - JUÇARA, 2021)
In the last forty years, feminist literary criticism have pointed out that Shakespeare questioned gender roles and defended women in his plays in a context of misogyny and exclusion of women. More recently, ecofeminist theorists such as Rebecca Laroche and Jennifer Munroe have argued that Shakespeare’s plays also destabilize the confines between humans and non-humans, which is an essential element to deconstruct complex gender issues. Adopting an ecofeminist approach, this essay purposes to analyse Viola’s character, the protagonist of Shakespeare’s Twelfth Night, aiming to demonstrate how her relationship to the marine world broadens the interpretation of cross-dressing. Firstly, it will introduce Val Plumwood’s deconstructionist ecofeminist theory and discuss the ways in which Early Modern views on the natural world can be insightful to an ecofeminist analysis. Secondly, supported by Dan Brayton’s Shakespeare’s Ocean, it will examine how Viola’s relationship to the marine world undermines gender roles and deconstructs the concept of “humanity” itself. Keywords: Shakespeare. Ecofeminism. Ecocriticism.